Pengaruh Penggunaan Lembar Kerja Siswa (LKS) Eksperimen Laju Reaksi Berbasis Inkuiri Terbimbing Terhadap Hasil Belajar Siswa Kelas XI MIA SMAN 4 Padang - Maida, Margarita Claudya; Bayharti, Bayharti; Andromeda, Andromeda (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2019)
This study aims to reveal the effect of using guided inquiry based experiment worksheet on reaction rate topic on students’ learning outcome. This research is a quasi-experimental research, using  randomized Posttest Only Control Group Design. The research sample consisted of two classes, namely the experiment class and control class obtained through cluster sampling technique. The population were students of class XI MIA SMAN 4 Padang as much as 6 classes, the academic year 2015/2016. Sample were class XI MIA 1 (experimental group) and class XI MIA 3 (control group). Learning outcome ware collected by tests at the end of the study. Data analysis showed that the experiments class learning with guided inquiry based experiment worksheet got learning outcome with average value of 86.27. Meanwhile learning outcomes of student in control class who learned without guided inquiry based experiment worksheet was 74.40. Both of Normality and Homogenous’s results showed that the distribution of the two experimental classes were normal and homogeneous. After the t-test on the real level of 0.05 was found that tcount is greater than ttable. It’s means that research hypothesis (H1) is accepted, so that it can be concluded that the results of student learning using student worksheet guided inquiry-based reaction rate is significantly higher than the student worksheet without a reaction rate-based guided inquiry.